2009
DOI: 10.1161/atvbaha.109.185694
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of SIRT1 in Diabetic Vascular Dysfunction

Abstract: Objective-Calorie restriction (CR) prolongs the lifespan of various species, ranging from yeasts to mice. In yeast, CR extends the lifespan by increasing the activity of silencing information regulator 2 (Sir2), an NAD ϩ -dependent deacetylase. SIRT1, a mammalian homolog of Sir2, has been reported to downregulate p53 activity and thereby prolong the lifespan of cells. Although recent evidence suggests a link between SIRT1 activity and metabolic homeostasis during CR, its pathological role in human disease is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
159
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(172 citation statements)
references
References 37 publications
9
159
2
2
Order By: Relevance
“…Mattagajasingh et al (17) demonstrated that inhibition of SIRT1 in rat arteries attenuated endothelium-dependent vasodilation, which might be due to the enhanced acetylation of endothelial nitric oxide synthase (eNOS). In mice, RSV administration increased aortic eNOS activity (18). Furthermore, EC-specific overexpression of SIRT1 decreased atherosclerosis in ApoE-knockout mice (19).…”
mentioning
confidence: 96%
“…Mattagajasingh et al (17) demonstrated that inhibition of SIRT1 in rat arteries attenuated endothelium-dependent vasodilation, which might be due to the enhanced acetylation of endothelial nitric oxide synthase (eNOS). In mice, RSV administration increased aortic eNOS activity (18). Furthermore, EC-specific overexpression of SIRT1 decreased atherosclerosis in ApoE-knockout mice (19).…”
mentioning
confidence: 96%
“…resveratorl restores acetylated p53 and p21 in the aorta and thus improves endothelial dysfunction by down-regulating ICAM-1 expression and inhibiting leukocyte rolling [101], These data imply a protective role of SIRT1 in the pathogenesis of diabetic vascular dysfunction .…”
Section: The Energy Sensor---sirt1mentioning
confidence: 70%
“…In Sirt1 knockout mice, insulin levels are reduced in both normoglycemic and glucose tolerance experiments. Consistently, in a type II diabetic mouse, genetic upregulation of SIRT1 [99,101] or treated with resveratorl [102], a small molecule activator of SIRT1, enhances insulin secretion and thus improves glucose tolerance.…”
Section: The Energy Sensor---sirt1mentioning
confidence: 75%
See 2 more Smart Citations